Assessment of adherence to antiretroviral therapy schemes containing dolutegravir in a municipality of Goiás (Research, Society and Development, 2021)
Individual infected with the Human Immunodeficiency Virus (HIV) have free access to Antiretroviral Therapy (ART), however for it to work it is necessary that the patient conducts the maintenance of the treatment, as the effectiveness of ART depends directly on the patient's compliance. The aim of the present study was to describe the adherence to ART of patients with HIV / AIDS treated by the Unified Health System in the State of Goiás. This is a cross-sectional descriptive study, developed at the health unit Dr. Ilion Fleury Jr., reference in diagnosis and treatment of STIs / AIDS in the city of Anápolis / GO. The “Survey for the assessment of adhesion to antiretroviral treatment - CEAT-HIV” was used to assess adherence to ART. The patients' medical records were analyzed to obtain laboratory results. Among the 88 patients included in the study, 74% (n = 65) were male, with a mean age of 37 years and 49% (n = 43) declared themselves to be heterosexual. When analyzing adherence, it was found that 81% (n = 72) had strict adherence, more than 87% of the participants had an undetectable viral load, with a TCD4 + lymphocyte count of ± 555 cells / mm³. The results of this study allow us to suggest a good adherence to the new ART scheme with dolutegravir, in addition to better viral load control.